Performance Evaluation of Red Clay Soils stabilized with Bluegum Sawdust Ash and Sisal Fiber as Low-Volume Road Sub-base Materials - Chinkhuntha, Wanangwa; Owayo, Alphonce; Ambassah, Nathaniel (Engineering, Technology & Applied Science Research, 2024)
The engineering properties of Red Clay Soils (RCS) in tropical regions are frequently inadequate for road construction due to a number of factors, including high compressibility, high creep rates, high plasticity, low strength, and swelling potential. This research project examines the potential of stabilizing RCS using Bluegum Sawdust Ash (BSDA) and Sisal Fiber (SF) to develop a cost-effective and environmentally sustainable material for use in low-volume roadways. Tests were conducted on both unstabilized and stabilized soil samples to evaluate a range of physical properties, including Atterberg limits, compaction, Unconfined Compressive Strength (UCS), and California Bearing Ratio (CBR). BSDA was introduced in increments from 2% to 10% at 2% intervals, with 6% of it being optimal. This resulted in a reduction in the Plasticity Index (PI) from 20.78% to 10.90% and a significant increase in both the UCS and the CBR values. The addition of SF resulted in further enhancement of stabilization, with an increase in the soaked CBR to 28.12% and UCS to 736.011 kN/m³. This triphasic approach, which combines RCS, BSDA, and SF, offers a sustainable and economical solution for the construction of road subbases in civil engineering.